A unified picture of hard-soft segmental development along olefin chain shuttling copolymerization. (12th October 2015) - Saeb, Mohammad Reza; Khorasani, Mohammad Mehdi; Ahmadi, Mostafa; Mohammadi, Yousef; Stadler, Florian J.
Abstract: It is the dual nature of chain shuttling polymerization (CSP) that makes control of olefin block copolymer (OBC) composition difficult and difficult, but at the same time, stimulating. Although recent investigations on OBCs brought some insights to the kinetics and microstructure of block copolymers differentiating from ethylene and α-olefins, some crucial features of these systems are not uncovered because of experimental difficulties. Thus, attention is still placed upon theoretical concepts that enable deeper understanding of behavior of end-of-batch OBCs. Extending the predictability of a well-developed Monte Carlo algorithm, we present for the first time an explicit image of hard-soft segmental growth at the course of CSP process. The stochastically tailored ethylene/1-octene copolymers with diverse architectural characteristics were simulated and characterized in terms of mole fraction of soft and hard segments, block length distribution, sequence length distribution, longest ethylene sequence distribution, and the distribution of the number of blocks per growing copolymer chain to be used as unique signatures of this reaction mechanism. Graphical abstract: A molecular-level image was captured from multiblock olefinic copolymers using Kinetic Monte Carlo simulation. Multifarious microstructural features were visualized among which distributions of number of blocks per chain, block length, and monomer sequence lengths are notable. Highlights: Detailed model simulating synthesis of olefinic block copolymers (OBC). Analysis of the resulting block structure. Extraction of physical properties determining parameters, e.g. sequence lengths. Model tunable to many dual catalysis systems.